Enhancement of thermal and techno-economic performance and prediction of drying kinetics of paddy dried in solar bubble dryer - Yogendra Kumar Jyoti; Sanjaya K Dash; Kalpana Rayaguru; Uma Sankar Pal; Nikita Mishra; P.N. Ananth; Suryakanta Khandai (Energy Nexus, 2023)
The development and performance evaluation of a solar Bubble drier (SBD) for drying agricultural produce are presented in this study. In order to evaluate the solar bubble dryer's performance in terms of drying characteristics and end-product economics, it was compared to the solar tunnel dryer (STD). A solar tunnel dryer is a structure with a tunnel-like shape that is covered in UV-stabilized polythene sheet so that industrial and agricultural items can be dried off. While there was no load, the maximum temperatures inside the solar bubble dryer and solar tunnel dryer were 56.25 and 49.30 °C, respectively. When there was a full load, the maximum temperatures inside the dryer were 49.55 and 33.20 °C, respectively. For solar bubble dryers, the average final moisture content ranged from 13.07±0.335 % to 18.74±0.716 % (w.b.), while for solar tunnel dryers, it ranged from 13.60±0.575 % to 20.60±0.751 % (w.b.). The mean drying rate also varied depending on the drying air temperature and air flow mode, ranging from 0.081±0.020 to 0.006±0.005 kg/kg dm-h for solar bubble dryers and 0.056±0.025 to 0.005±0.002 kg/kg dm-h for solar tunnel dryers. The thermal efficiency of the developed dryer was found to be 58.39% for solar bubble dryers and 48.09% for solar tunnel dryers, which are significantly higher than that of other general Sun drying (36%). However, the drying rate varied between 0.081 to 0.006 g of water evaporated per g of dry matter per hour when solar bubble dryer was adopted and 0.014 to 0.007 g for solar tunnel dryer. Economic analysis showed that the SBD and STD had payback periods of 3.23 and 2.54 years, respectively. However, the cost of drying came lower for the SBD than the STD, which were Rs. 1.51 per kg and Rs. 1.76 per kg.